Tracing the future of food systems transformation with foresight analysis - International Rice Research Institute (CGIAR, 2023)
Manila, Philippines (23 October 2023) – Forward-thinking policies focusing on the impacts of recent political and environmental shocks and addressing gender and social inclusion vulnerabilities are important in sustaining local and global solutions to food and nutrition security under climate change. This was the theme of the Foresight to Accelerate Food Systems Transformation side event at the recently concluded 6th International Rice Congress.